2015
DOI: 10.1088/0022-3727/48/8/085101
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic on-chip integration of semiconductor waveguides, beamsplitters and single-photon sources

Abstract: The implementation of a fully integrated Hadamard gate on one single chip is currently one of the major goals in the quantum computation and communication community. Prerequisites for such a chip are the integration of single-photon sources and detectors into waveguide structures such as photonic crystals or slab and ridge waveguide. Here, we present an implementation of a single-photon on-chip experiment based on a III-V semiconductor platform.Individual semiconductor quantum dots were used as pulsed single-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…15,16 It has been demonstrated that very high coupling efficiencies of quantum emitters into photonic crystals (PCs) are possible 17,18 and a high coupling to ridge WGs can also be expected. 19 Together with the implementation of beamsplitters (BSs) 20,21 or single-photon detectors, 22,23 several building blocks for on-chip LOQC have been realized. For the LOQC scheme, it is furthermore necessary to achieve a two-photon quantum interference with indistinguishable photons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 It has been demonstrated that very high coupling efficiencies of quantum emitters into photonic crystals (PCs) are possible 17,18 and a high coupling to ridge WGs can also be expected. 19 Together with the implementation of beamsplitters (BSs) 20,21 or single-photon detectors, 22,23 several building blocks for on-chip LOQC have been realized. For the LOQC scheme, it is furthermore necessary to achieve a two-photon quantum interference with indistinguishable photons.…”
mentioning
confidence: 99%
“…A more detailed description of the measurement method can be found in Ref. 21. The overall propagation length of the photons between the excitation and the out-coupling is approximately 430-450 lm.…”
mentioning
confidence: 99%
“…For these reasons, sources producing different quantum states while maintaining a high degree of compactness and integratability are highly desirable. GaAs and its material derivatives like AlGaAs present a strong case for the miniaturization of different quantum components in the same chip [21]. Its direct bandgap has already led to the monolithic integration of the primary laser source and the nonlinear medium into a single device emitting photon pairs under electrical injection at room temperature [22].…”
mentioning
confidence: 99%
“…To fully exploit the advantages of integrated photonics, it would be ideal to integrate these different components on a single substrate. Motivated by this, many researchers have recently demonstrated the hybrid integration of different quantum-optical components [103][104][105][106][107][108][109]. Hence, the stage of integrated quantum photonics research is now moving to hybrid integration on a chip.…”
Section: On-chip Quantum Buffermentioning
confidence: 99%